A Review on Medicinal Plants Used in Treatment of Obesity and Overweight - S Kianbakht (Institue of Medicinal Plants, ACECR, 2010)
The prevalence of obesity and overweight is alarmingly increasing. Obesity and overweight are regarded as the most important avoidable risk factors causing morbidity and mortality. The approved synthetic weight loss drugs have low efficacies and considerable adverse effects. Numerous approaches are used as alternatives to synthetic drugs to induce weight loss. One of the approaches is use of herbal medications. Here, the effects of medicinal plants and herbal active constituents including caffeine, ephedrine, Garcinia cambogia, Hoodia gordonii, tea (green, black and oolong), Citrius aurantium, capsaicin, plant fibers such as guar gum, glucomannan and psyllium, Cissus quadrangularis, Irvingia gabonensis, Phaseolus vulgaris, chitosan, Trigonella foenum-graecum and yohimbine in clinical trials concerning weight loss are reviewed. Most of these medicinal plants have been studied in very limited clinical studies, and none have been evaluated to the extent that can be definitively recommended for weight reduction, nor have they been studied to ascertain the extent of potential hazards. Thus, further clinical researches to define the efficacies and safeties of the medicinal plants and herbal active constituents that may have weight reducing properties seem warranted.